Exploring Effective Teacher-Student Interpersonal Interaction Strategies in English as a Foreign Language Listening and Speaking Class - Ding, Jie (Frontiers in Psychology, 2021)
The main purpose of English learning is to communicate and interact in global contexts. However, in EFL contexts as in China, most of the students have limited interactional competence in contrast to their grammatical and structural competence. The reason is that Chinese classrooms mostly lack an interactional climate. This calls for an urgent need to develop interpersonal interaction skills by EFL teachers via appropriate strategies. To this end, this article presents an overview of nine interpersonal communication skills/strategies which are pivotal in L2 education. It also describes their definitions and related theories. Moreover, the outcomes of such strategies in aural skills are also explained. Finally, implications, research gaps, and future avenues for research are provided.